Skin color profile capture for scale and rotation invariant hand gesture recognition - Bastos, R.; Dias, J. (Gesture-Based Human-Computer Interaction and Simulation, Revised Selected Papers from 7th International Workshop on Gesture in Human-Computer Interaction and Simulation 2007, GW2007, ISCTE, Lisbon, May 2007, 2009)
This paper presents a new approach to real-time scale and rotation invariant hand pose detection, which is based on a technique for computing the best hand skin color segmentation map. This segmentation map, a vector entity referred to as a “skin profile”, is used during an online hand gesture calibration stage to enable correct classification of skin regions. Subsequently, we construct efficient and reliable scale and rotation invariant hand pose gesture descriptors, by introducing an innovative technique, referred to as “oriented gesture descriptors”. Finally, hand pose gesture recognition is computed using a template matching technique which is luminance invariant.